2021
DOI: 10.1186/s12879-021-06850-w
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus-associated anal squamous intraepithelial lesions in men who have sex with men and transgender women living with and without HIV in Karachi Pakistan: implications for screening and prevention

Abstract: Background Anal squamous intraepithelial lesions (ASIL), strongly related to human papilloma virus (HPV) infection, is more prevalent among men who have sex with men (MSM). However, no such data are available for Pakistan yet, and neither HPV vaccination nor anal-cytology screening is implemented in Pakistan. The purpose of this first ever study was to assess the prevalence of HPV-related anal cytological abnormalities among MSM and transgender women living with and without HIV infection in Pak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 76 publications
(81 reference statements)
0
10
1
Order By: Relevance
“… 32 The observed significant association between anal HSIL and history of infection with any gonorrhoea in our data was surprising. However, studies have reported that sexually transmitted infections (STIs) such as chlamydia and gonorrhoea increased the risk of anal squamous intraepithelial lesions 28 and anal cancer. 33 Moreover, McCloskey et al reported that the seropositivity for HIV, HSV-2, T. pallidum , HBV, and HCV and history of gonorrhoea or chlamydia exert a powerful amplifying factor increasing the risk of anal HSIL above the risk of HR-HPV infection alone in both HIV-positive and HIV-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“… 32 The observed significant association between anal HSIL and history of infection with any gonorrhoea in our data was surprising. However, studies have reported that sexually transmitted infections (STIs) such as chlamydia and gonorrhoea increased the risk of anal squamous intraepithelial lesions 28 and anal cancer. 33 Moreover, McCloskey et al reported that the seropositivity for HIV, HSV-2, T. pallidum , HBV, and HCV and history of gonorrhoea or chlamydia exert a powerful amplifying factor increasing the risk of anal HSIL above the risk of HR-HPV infection alone in both HIV-positive and HIV-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of participants tested positive for HIV or another STI (HSV-2, syphilis, gonorrhea, orchlamydia) in a cross-sectional community-based study of MSM in Hanoi, Vietnam, and the prevalence of HIV, HSV-2, syphilis, gonorrhea, and chlamydia was 10%, 4%, 13%, 34%, and 19%, respectively [ 19 ]. Overall HPV infection prevalence among MSM and TGW was 66.4% in Pakistan, and the substantial risk of them to develop anal cancer was high, particularly for those with a concurrent HIV infection [ 20 ]. In Japan, the overall prevalence of high-risk human papillomavirus positivity was 59.7%, with HIV-infected MSM (68.9%) having a significantly higher rate than HIV-uninfected MSM (40.6%) [ 21 ].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Certain at-risk groups such as gay, bisexual, and other men who have sex with men (MSM) particularly those MSM who are infected with HIV are at increased risk of HPV infection and are disproportionately affected by HPV associated genital warts, anal cancer and its precursor high-grade squamous intraepithelial lesions [ 5 ]. Recently study conducted in Pakistan by our group found 65% prevalence of HPV infection [ 6 ] and 35% of anal precancerous lesions [ 7 ] in MSM and transgender women living with and without HIV. HPV infection is an important risk factor for both cervical and anal cancers and causes similar type of squamous intraepithelial precancerous lesions, cervical intraepithelial neoplasia (CIN) and anal intraepithelial neoplasia (AIN), respectively.…”
Section: Introductionmentioning
confidence: 99%